Finite element analysis and optimization of foam filled fender under quasi static and dynamic responses - Djamaluddin, F. (Frontiers in Mechanical Engineering, 2023)
Mainly composed of elastic materials, ship fenders are utilised on all kinds of vessels for the protection of berthing structures and the prevention of damage due to heavy crash loads. In this study, six (6) models of a conventional ship fender's structure that have varied geometric dimensions were examined for crashworthiness design and energy absorption properties. Moreover, the study evaluated crushing force efficiency (CFE) and specific energy absorption (SEA); four fender design variables (height, foam density, thickness, and material) were also assessed for optimisation. First, an analysis of non-linear finite elements is conducted with the use of explicit ABAQUS for estimating crash reactions; the results are then compared to an appropriate reference. Consequently, this study aims to enhance aluminium foam-filled fenders' crashworthiness indicators when they are impacted quasi-static and dynamic loadings. An NSGA II (Non-dominated Sorting Genetic Algorithm II) multi-objective approach was used to obtain the optimum Pareto solutions for the maximum of Specific Energy Absorption (SEA) and the minimum of Crushing Force Efficiency (CFE). Based on the results of the optimisation, the best performance was observed in model 5; however, changing the traditional fender design is advised.